OsPT2, a phosphate transporter, is involved in the active uptake of selenite in rice. Issue 4 (11th November 2013) - Zhang, Lianhe; Hu, Bin; Li, Wei; Che, Ronghui; Deng, Kun; Li, Hua; Yu, Feiyan; Ling, Hongqing; Li, Youjun; Chu, Chengcai
Summary: Selenite is a predominant form of selenium (Se) available to plants, especially in anaerobic soils, but the molecular mechanism of selenite uptake by plants is not well understood. ltn1, a rice mutant previously shown to have increased phosphate (Pi) uptake, was found to exhibit higher selenite uptake than the wild‐type in both concentration‐ and time‐dependent selenite uptake assays. Respiratory inhibitors significantly inhibited selenite uptake in the wildtype and the ltn1 mutant, indicating that selenite uptake was coupled with H + and energy‐dependent. Selenite uptake was greatly enhanced under Pi‐starvation conditions, suggesting that Pi transporters are involved in selenite uptake. OsPT2, the most abundantly expressed Pi transporter in the roots, is also significantly up‐regulated in ltn1 and dramatically induced by Pi starvation. OsPT2 ‐ overexpressing and knockdown plants displayed significantly increased and decreased rates of selenite uptake, respectively, suggesting that OsPT2 plays a crucial role in selenite uptake. Se content in rice grains also increased significantly in OsPT2 ‐ overexpressing plants. These data strongly demonstrate that selenite and Pi share similar uptake mechanisms and that OsPT2 is involved in selenite uptake, which provides a potential strategy for breeding Se‐enriched rice varieties.